A Systematic Evidence‐Based Review Regarding miRNA Polymorphisms in Recurrent Implantation Failure - Bogdan Doroftei; Ovidiu‐Dumitru Ilie; Ana‐Maria Dabuleanu; Mara Doroftei; Ciprian Ilea; Sergiu Timofeiov; Anca Bivoleanu; Elena Tataranu (Reproductive Medicine and Biology)
ABSTRACT Background This systematic review aimed to evaluate whether specific single nucleotide polymorphisms (SNPs) in miRNAs are associated with recurrent implantation failure (RIF). Methods A comprehensive literature search was conducted across PubMed‐MEDLINE, Web of Science, Scopus, and the Excerpta Medica DataBASE. Results The Newcastle‐Ottawa Scale (NOS) yielded an intermediate to high quality, with one study rated with 6 stars, and the remaining four with 7 stars. RIF risk‐related genotypes included miR‐196a, miR‐449b, miR‐34a, miR‐146aCG+GG‐miR‐196a2CC, miR‐149TT‐miR‐196a2CC, miR‐196a2CC‐miR‐499AA, miR‐608GC‐miR‐938CC, miR‐27aAG‐miR‐423CC/miR‐604AG/GG and miR‐34aC>A AA‐miR‐130aG>A GG. Protective combinations included miR‐1302‐3, miR‐631II‐miR‐1302‐3CT, and miR‐938CC‐miR‐1302‐3CT. Protective allele combinations G‐T‐T‐A, C‐T, T‐T‐G, T‐T and G‐C‐A‐G, G‐A‐G, A‐G‐G were less frequent in RIF cases, whereas A‐T‐C, T‐C‐C‐T, T‐C‐T, A‐C‐G‐A, A‐A‐G‐G, G‐A‐A‐A, A‐A‐C‐A and G‐G‐A haplotypes were more commonly associated with increased risk. Notably, miR‐608 GC+CC, miR‐1302‐3 CC, miR‐27a AG+GG, miR‐423 CA+AA, miR‐604 AG+GG, miR‐222 GT+TT, and miR‐34a GA+AA were associated with altered coagulation parameters. Additionally, miR‐222 correlated with decreased creatinine levels, the G>T mutation with elevated follicle‐stimulating hormone (FSH), miR‐34aC>A AA genotype with reduced thyroid‐stimulating hormone (TSH) levels, and CA+AA with increased blood urea nitrogen (BUN) levels. Conclusions This systematic review highlights that specific miRNA SNPs and haplotype combinations are significantly associated with either increased susceptibility to or protection against RIF.